Antibiotics enhancing drug-induced liver injury assessed for causality using Roussel Uclaf Causality Assessment Method: Emerging role of gut microbiota dysbiosis - Fu, Lihong; Qian, Yihan; Shang, Zhi; Sun, Xuehua; Kong, Xiaoni; Gao, Yueqiu (Frontiers in Medicine, 2022)
Drug-induced liver injury (DILI) remains a disease that is difficult to predict and prevent in clinical perspective, as its occurrence is hard to fully explain by the traditional mechanism. In recent years, the risk of the DILI for microbiota dysbiosis has been recognized as a multifactorial process. Antibiotics directly affect the structure and diversity of gut microbiota (GM) and changes in metabolites. The depletion of probiotics after antibiotic interference can reduce the efficacy of hepatoprotective agents, also manifesting as liver injury. Follow-up with liver function examination is essential during the administration of drugs that affect intestinal microorganisms and their metabolic activities, such as antibiotics, especially in patients on a high-fat diet. In the meantime, altering the GM to reconstruct the hepatotoxicity of drugs by exhausting harmful bacteria and supplementing with probiotics/prebiotics are potential therapeutic approaches. This review will provide an overview of the current evidence between gut microbiota and DILI events, and discuss the potential mechanisms of gut microbiota-mediated drug interactions. Finally, this review also provides the insights into the "double-edged sword" effect of antibiotics treatment against DILI and the potential prevention and therapeutic strategies.